Stress urinary incontinence is highly prevalent in recreationally active women attending gyms or exercise classes - McKenzie, S.; Watson, T.; Thompson, Judith; Briffa, Kathy (2016)
Introduction and hypothesis: The purpose of this study was to determine the prevalence of stress urinary incontinence (SUI) in recreationally active women attending gyms or exercise classes. Methods: Data were collected on the frequency and severity of incontinence and the prevalence of SUI risk factors; screening for PFM dysfunction in a fitness appraisal; symptom modification strategies; knowledge of pelvic floor muscle (PFM) exercises and the Pelvic Floor First (PFF) initiative. Three hundred and sixty-one women aged 18–83 who attended exercise classes or gyms in Western Australia were surveyed. Results: Nearly half (49.3 %) of participants reported SUI, the majority of whom slight or moderate leakage. Ninety-six per cent reported at least one SUI risk factor, with the mean being 2.7 (SD = 1.4). Almost all women surveyed had heard of PFM exercises (97.2 %), but only 15.2 % of participants were screened for PFM dysfunction in a fitness appraisal. Forty-three per cent reported that a fitness instructor cued PFM activation during a workout. Less than 1 in 10 (9.7 %) of the women surveyed had heard about the PFF initiative. Conclusion: Urinary incontinence is common in women attending gyms or exercise classes, but is rarely screened for. More education is required to encourage fitness leaders to screen exercise participants and to provide PFM-’friendly” modifications.